2019
DOI: 10.4103/jips.jips_71_19
|View full text |Cite
|
Sign up to set email alerts
|

Microcomputed tomography a noninvasive method to evaluate the fit of a restoration as compared to conventional replica technique

Abstract: Aim: The aim of the study was to compare the assessment methods used to evaluate the fit of Ni-Cr metal copings. Settings and Design: Comparative- Invitro study design. Materials and Methods: A stainless steel die simulating a prepared first maxillary premolar was used as a master die. Wax pattern copings were fabricated by the conventional dipping wax technique ( n = 20) on the master die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Our results showed that the marginal fit of both copings was similar, but internal fit was better for cast copings. The higher values obtained for the occlusal surface when compared with the axial wall are also described in previous studies 13,20,21,24 , despite the fact that milled copings are believed to have lower marginal discrepancies, since their fabrication has fewer steps. According to the literature, cement film thickness varies considerably, but most authors describe 120 µm as the clinically acceptable maximum thickness for a long-term good prognosis 25 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results showed that the marginal fit of both copings was similar, but internal fit was better for cast copings. The higher values obtained for the occlusal surface when compared with the axial wall are also described in previous studies 13,20,21,24 , despite the fact that milled copings are believed to have lower marginal discrepancies, since their fabrication has fewer steps. According to the literature, cement film thickness varies considerably, but most authors describe 120 µm as the clinically acceptable maximum thickness for a long-term good prognosis 25 .…”
Section: Discussionsupporting
confidence: 79%
“…Lately, micro-CT imaging has also been used to assess the marginal and internal fit of crowns and fixed partial dentures 11,28,39 . Both non-destructive methods are considered effective to evaluate the adaptation of indirect restorations 20,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary CoCr alloys have gained popularity as compared with conventional gold alloys due to improved corrosion resistance and low cost [23]. The available literature showed multiple techniques, i.e., the direct-view measurement technique, the silicone replica technique, and cross-sectioning to measure the marginal misfit of fabricated copings [26]. The micro-computed tomography (CT), on the other hand, is comparatively an advanced method to assess the fit of indirect restoration through processing of scanned specimens slices, reconstructing the assembly by using software and gaging the misfit [27].…”
Section: Discussionmentioning
confidence: 99%
“…1,10,12,20 In the present study, the measurement of the thickness and volume of the silicone specimens was made by micro-CT technique due to its advantages to other analog or digital measurement techniques (for example, methods using gauges, microscopes, or scanners), such as specimen preservation, high-resolution power, high precision, simple methodology, specimen digitization by just one scan, and the ability to measure the total thickness and simultaneously the volume of the specimen. 1,[10][11][12][21][22][23] No differences in thickness and volume were found between the two groups of frameworks, so the null hypothesis could not be rejected. These findings are in line with the results of a previous laboratory study, 1 whose authors also did not declare differences in the fit accuracy of RPD metal frameworks produced by a similar CAD-CAM protocol with those produced by a conventional protocol.…”
Section: Discussionmentioning
confidence: 99%